Nonlinear elastic analysis of steel planar frames under fire loads. (1st April 2015) - Luongo, Angelo; Contento, Alessandro
Highlights: The nonlinear elastic problem for a planar frame subjected to thermal loadings is resolved here. The elastic law accounts for thermal deformations and for temperature-dependence of the elastic modulus. The elastic problem is formulated in a mixed equilibrium-compatibility form. After integration of the field equation an 'exact' finite element is derived. The nonlinear algebraic problem is solved numerically by the Newton–Raphson procedure. Abstract: The nonlinear elastic problem for planar frames, made of rectilinear beams subjected to thermal loadings, is resolved here. The basic element is an Euler–Bernoulli beam, whose elongation is a nonlinear function of the displacements. The elastic law accounts for thermal deformations and for temperature-dependence of the elastic modulus. The elastic problem is formulated in a mixed equilibrium-compatibility form and an 'exact' finite element is derived. Assembling the element relations, the governing equations for the frame are recast in a discrete form. The nonlinear algebraic problem is solved numerically and results are compared with those provided by a FE software.